ОРГАНІЗАЦІЯ ГРУПОВОЇ РОБОТИ НА ЗАНЯТТЯХ З ГЕОГРАФІЧНИХ ДИСЦИПЛІН - Гaнчук, O.V. (Educational Dimension, 2009)
In article problems of the organization of group work on occupations from geographical disciplines are considered.